A novel risk stratification model based on tumor size and multifocality to predict recurrence in pediatric PTC: comparison with adult PTC - Du, Rui; Zhang, Ying; Kou, Jiedong; Li, Jingting; Sui, Chengqiu; Zhang, Daqi; Fu, Yantao; Zhou, Le; Fu, Qingfeng; Li, Fang; Dionigi, Gianlorenzo; Liang, Nan; et al. (Frontiers in Endocrinology, 2024)
In this study, two important clinical features-tumor size and multifocality-were included as key factors in the RRS method. The study found that this new method can clearly distinguish patients with pediatric PTC with different levels of recurrence risk. This new method provides a quick and efficient tool for clinicians to evaluate the recurrence risk in patients with pediatric PTC in clinical practice and facilitate decision-making regarding appropriate treatment strategies.1. This study not only analyzed the pathological characteristics of pediatric PTC, but also analyzed the risk factors affecting the metastasis of central cervical lymph nodes, lateral cervical lymph nodes and recurrence in children. In pediatric PTC, younger age, male, larger tumor size, multifocality are more likely to metastasise to the cervical lymph nodes. A tumor size of ≥1 cm and multifocality are independent risk factors for the recurrence of pediatric PTC, whereas the independent risk factor for adult recurrence is only LLNM.2. Through direct comparison with adult PTC, this study found the differences of pathological characteristics and recurrence risk factor between pediatric PTC and adult PTC.3. A new risk stratification method for recurrence was developed, which can effectively predict the prognosis of pediatric PTC. The novel children's RRS method based on tumor size and multifocality performed well in predicting pediatric PTC recurrence. This new method provides a quick and efficient tool for clinicians to evaluate the recurrence risk of patients with pediatric PTC in clinical practice and facilitate decision-making regarding appropriate treatment strategies.The study was conducted in accordance with the Declaration of Helsinki and approved by the China-Japan Union Hospital Institutional Review Board (No. 20220804012). Informed consent was obtained from the participants or their guardians. The study was conducted in accordance with the Declaration of Helsinki. Informed consent was obtained from all patients. Written